Star wars. Episode III Revenge of the Sith . - 2lcgft1# Lucas, George, 1944-; McCallum, Rick, 195; McGregor, Ewan; Portman, Nata 1971-; Christensen, Hay 1981-; Copyright Collection (Lib 1981- (United States 20th Century Fox)
After three years of fighting in the Clone Wars, Anakin Skywalker succumbs to the Dark Side of the Force, completing his tragic transformation into Darth Vader, Lord of t
c2005.## Copyright: Lucasfilm, Ltd. Prev. reg.: Screenplay prev. reg. 2004, PAu 2-809-087. NM: all other cinematographic material, incl. music. DCR 2005; PUB 2May05; REG 4May05; PA1-2
Summary taken from Internet movie
No
Sources used: copyright data base; copyright data sheet; Internet movie database, 9/19/2005; Variety
Executive producer, George Lucas ; camera, David Tattersall ; editors, Roger Barton, Ben Burtt ; music, John Williams ; production designer, Gavin Bocquet ; special visual effects and animation, Industrial Light
Ewan McGregor, Natalie Portman, Hayden Christensen, Ian McDiarmid, Samuel L. Jackson, Christoph
Keywords: Action and adventure f; Science fiction f